2020
DOI: 10.3390/su12124986
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Links between Organizational Factors and Perceptions of Community Sustainability Performance: An Empirical Investigation of Community-Based Nongovernmental Organizations

Abstract: Community-based nongovernmental organizations have emerged as leaders in local economic development, with a growing capacity for undertaking community sustainability projects in distressed neighborhoods. Very little is known about what organizational and managerial characteristics contribute to community sustainability performance. This article seeks to address this gap in the literature. Survey data from 134 community action agencies in the U.S. were analyzed to determine which organizational and managerial f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 88 publications
0
9
0
Order By: Relevance
“…Along these lines, returning JPNA editorial board member Nathanial Wright and his coauthor remind us that community-based nongovernmental organizations have emerged as leaders in local economic development, as they have increased their capacity for undertaking community sustainability projects (Wright & Reames, 2020). Through a survey of 134 community action agencies, the authors found that community engagement, human resource capacity, government collaboration, government funding, and revenue diversification help to determine the effectiveness of community sustainability performance (Wright & Reames, 2020). On the other hand, the authors caution that too much reliance on government funding might negatively impact the ability of community based nonprofits to achieve their community sustainability goals, as well as limit their important societal and democratic roles (Wright & Reames, 2020).…”
Section: Resiliencymentioning
confidence: 99%
See 1 more Smart Citation
“…Along these lines, returning JPNA editorial board member Nathanial Wright and his coauthor remind us that community-based nongovernmental organizations have emerged as leaders in local economic development, as they have increased their capacity for undertaking community sustainability projects (Wright & Reames, 2020). Through a survey of 134 community action agencies, the authors found that community engagement, human resource capacity, government collaboration, government funding, and revenue diversification help to determine the effectiveness of community sustainability performance (Wright & Reames, 2020). On the other hand, the authors caution that too much reliance on government funding might negatively impact the ability of community based nonprofits to achieve their community sustainability goals, as well as limit their important societal and democratic roles (Wright & Reames, 2020).…”
Section: Resiliencymentioning
confidence: 99%
“…Through a survey of 134 community action agencies, the authors found that community engagement, human resource capacity, government collaboration, government funding, and revenue diversification help to determine the effectiveness of community sustainability performance (Wright & Reames, 2020). On the other hand, the authors caution that too much reliance on government funding might negatively impact the ability of community based nonprofits to achieve their community sustainability goals, as well as limit their important societal and democratic roles (Wright & Reames, 2020).…”
Section: Resiliencymentioning
confidence: 99%
“…Therefore, if the social equity pillar of sustainability is not carried out by government, then by whom shall it be pursued in efforts to create more sustainable communities? Community-based organizations (CBOs), a type of NGO providing services or other assistance to economically or socially disadvantaged persons within its designated community, have emerged as local leaders with growing capacity for pursuing projects that support community sustainability [20,21]. CBOs are critical to the effectiveness of creating community sustainability [20].…”
Section: Introductionmentioning
confidence: 99%
“…Community-based organizations (CBOs), a type of NGO providing services or other assistance to economically or socially disadvantaged persons within its designated community, have emerged as local leaders with growing capacity for pursuing projects that support community sustainability [20,21]. CBOs are critical to the effectiveness of creating community sustainability [20]. A city's commitment to sustainability is strongly linked to the advocacy of CBOs in the policy making process [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation